Perbandingan Konsep Anjak Piutang Syariah DSN-MUI dan Konsep Akad Hiwalah Dalam Surat Edaran Bank Indonesia - Octaviani, Baerin (Fakultas Syariah, 2015)
The purpose of this study is to discover the concept of sharia factoring in fatwa of DSN-MUI with the concept of Hiwalah contract in Bank Indonesia Circular Letter as well as the similarities and the differences between the concept of sharia factoring in fatwa of DSN-MUI with the concept of Hiwalah contract in Bank Indonesia Circular Letter. This study uses normative juridical research with conceptual approach and statute approach. The concept of sharia factoring in fatwa of DSN-MUI uses wakalah bil ujrah, and the concept of Hiwalah contract in Bank Indonesia Circular Letter is the concept of debt transfer with Hiwalah muthlaqah and Hiwalah muqayyadah. There are similarities between the concept of sharia factoring in fatwa of DSN-MUI with the concept of Hiwalah contract in Bank Indonesia Circular Letter. Those are from the aspect definition, object, other types, agreement form to give a bailout (qardh) and get ujrah/fees, and its term in the Civil Code is cessie and subrogation. While the differences between the concept of sharia factoring in fatwa of DSN-MUI with the concept of Hiwalah contract in Bank Indonesia Circular Letter are the form of debt transfer and receivable transfer, the assignor, related institutions, object of transaction, and the differences with Hiwalah muqayyadah are not provide bailout and get ujrah, as well as the settlement of dispute. Tujuan dari penelitian ini adalah untuk menemukan konsep anjak syariah di fatwa DSN-MUI dengan konsep kontrak Hiwalah dalam Surat Edaran Bank Indonesia serta persamaan dan perbedaan antara konsep anjak syariah di fatwa DSN-MUI dengan konsep kontrak Hiwalah dalam Surat Edaran Bank Indonesia. Penelitian ini menggunakan penelitian yuridis normatif dengan pendekatan konseptual dan pendekatan undang-undang. Konsep anjak syariah di fatwa DSN-MUI menggunakan wakalah bil ujrah, dan konsep kontrak Hiwalah dalam Surat Edaran Bank Indonesia adalah konsep transfer utang dengan Hiwalah muthlaqah dan Hiwalah muqayyadah. Ada kesamaan antara konsep anjak syariah di fatwa DSN MUI dengan konsep kontrak Hiwalah dalam Surat Edaran Bank Indonesia. Mereka adalah dari definisi aspek, objek, jenis lainnya, bentuk kesepakatan untuk memberikan bailout (qardh) dan mendapatkan ujrah / biaya, dan jangka dalam KUHPerdata adalah cessie dan subrogasi. Sedangkan perbedaan antara konsep anjak syariah di fatwa DSN-MUI dengan konsep kontrak Hiwalah dalam Surat Edaran Bank Indonesia adalah bentuk transfer utang dan pengalihan piutang, pemberi tugas, instansi terkait, objek transaksi, dan perbedaan dengan Hiwalah muqayyadah tidak memberikan bailout dan ujrah, serta penyelesaian sengketa.